Psychosocial concomitants to dental fear and behaviour management problems - ANNIKA GUSTAFSSON, KRISTINA ARNRUP, ANDERS G. BROBERG, LENNART BODIN, & ULF BERGGREN (IAPD and Blackwell, 2007)
Research on dental treatment problems among children uses different constructs.